2022
DOI: 10.3390/ijerph20010216
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Cultural Insights, a Nationwide Study Based on Repetitive Surveys of WHO Behavioral Insights Tool in Greece Regarding COVID-19 Pandemic and Vaccine Acceptance

Abstract: Monitoring behavioral and cultural insights during the pandemic is a useful tool to identify factors related to COVID-19 vaccine acceptance and confront the pandemic’s vast impact. Data were collected using a questionnaire designed according to the “survey tool and guidance” provided by the World Health Organization (WHO). Surveys were conducted by a market research company for five consecutive months, with a sample of 1000 individuals recruited per survey. Vaccination acceptance increased from 55.2% to 67.2%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the week leading up to the poll, the most common COVID-19 prevention measures adopted by households were hand washing with soap and clean water (83.5%) and wearing a face mask (48.5%), followed by staying at home (45.5%) and using alcohol-based sanitizers (Prezerakos et al, 2023). Qualitative data analysis from the focus groups confirmed that study participants knew about COVID-19 prevention strategies.…”
Section: Lusaka (Zambia)mentioning
confidence: 84%
“…In the week leading up to the poll, the most common COVID-19 prevention measures adopted by households were hand washing with soap and clean water (83.5%) and wearing a face mask (48.5%), followed by staying at home (45.5%) and using alcohol-based sanitizers (Prezerakos et al, 2023). Qualitative data analysis from the focus groups confirmed that study participants knew about COVID-19 prevention strategies.…”
Section: Lusaka (Zambia)mentioning
confidence: 84%
“…In these populations, the phenomenon of vaccine hesitancy and refusal has only been investigated either regionally or based on convenience samples, making recruiting participants accessible to researchers conducting these studies [ 26 , 61 , 62 , 65 ]. These previous studies are usually not in the appropriate depth [ 66 ] or do not systematically investigate social inequality [ 28 , 67 ]. In contrast, our approach involves the recruitment of participants from different settings, regions, and socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…Administrative measures that aided the implementation of public health interventions had varying effects. [42] While in Poland, public health was legally prioritized over individual liberties [43], punitive administrative measures taken against those who violated the regulations were cancelled in Romania due to some legal inconsistencies. In this context, 1.4% of respondents chose to vaccinate because they were afraid of the authorities.…”
Section: H12mentioning
confidence: 99%